2014
DOI: 10.12691/aees-2-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Structure in Soils Amended With Glyphosate-tolerant Soybean Residue

Abstract: Glyphosate is a broad-spectrum herbicide used extensively worldwide to control broadleaf weeds in agriculture. Research suggests that repeated application causes a change in soil microbial properties which could be affecting soil quality and productivity. Although glyphosate is generally regarded as having relatively low environmental impact, after 10 or more years of widespread use, field observations by farmers and emerging research suggest that long-term glyphosate tolerant (GT) cropping is having cumulativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, even sorbed glyphosate might be available to microbial degradation (32). Additionally, it has been suggested that microbial populations in soils with a history of glyphosate exposure have adapted and can better tolerate (i.e., are less responsive) or more rapidly break down (i.e., are more responsive to) the herbicide (24,25,29,33).…”
mentioning
confidence: 99%
“…However, even sorbed glyphosate might be available to microbial degradation (32). Additionally, it has been suggested that microbial populations in soils with a history of glyphosate exposure have adapted and can better tolerate (i.e., are less responsive) or more rapidly break down (i.e., are more responsive to) the herbicide (24,25,29,33).…”
mentioning
confidence: 99%
“…The two glyphosate formulations tested had little or no effect on the microbial groups quantified. In this experiment, the general absence of an effect, even at twice the maximum allowed dose, may be associated to the strong adsorption of glyphosate by Fe and Al oxides and clay (Nye et al, 2014), all of which were major components of the soil used in this experiment (clay >70%; AlO3 24%; Fe2O3 25%).…”
Section: Resultsmentioning
confidence: 79%
“…Although specific for plants, herbicides not only affect the target organisms, but may also alter the ecological balance directly or indirectly (Nye et al, 2014). However, they can be biodegraded or mineralised in the environment, being of great importance for bioremediation of both soil and environment (Singh et al, 2004;Ramos and Yoshioka 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation